SOME NOTES ON MELANOPSIDAE (GASTROPODA) OF MESOPOTAMIA - NASER, MURTADA D. (Iraqi Journal of Aquaculture, 2022)
An investigation to clarify some obscurity about Melanopsidae was performed on specimens collected from different sites of the South of Iraq. Three different morphs were recognized, two are widespread: Melanopsis costata and Melanopsis nodosa, the other Melanopsis subtingitana has a narrow distributions. Key words: Melanopsidae; Melanopsis costata; Melanopsis nodosa; Melanopsis subtingitana; South of Iraq